2022
DOI: 10.2147/ijnrd.s353213
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phosphorus and Pill Burden Among Hemodialysis Patients Prescribed Sucroferric Oxyhydroxide: One-Year Follow-Up on a Contemporary Cohort

Abstract: In prior analyses of real-world cohorts of hemodialysis patients switched from one phosphate binder (PB) to sucroferric oxyhydroxide (SO), SO therapy has been associated with improvements in serum phosphorus (sP) and reductions in daily PB pill burden. To characterize how SO initiation patterns have changed over time, we examined the long-term effectiveness of SO in a contemporary (2018-2019) cohort. Patients and Methods: Adult Fresenius Kidney Care hemodialysis patients first prescribed SO monotherapy as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In this real-world retrospective cohort study, PD patients prescribed SO as part of routine clinical care over a 1-year period experienced significant reductions in sP and PB pills per day, and increases in the percentage of patients who achieved sP ≤ 5.5 mg/dL or sP ≤ 4.5 mg/dL, suggesting improved sP management with a concurrent reduction in pill burden. These findings are consistent with our observations in a smaller cohort of patients on PD in 2014–2015 and the results of previous studies in patients on PD or hemodialysis [ 11 13 , 15 , 16 ]. Compared to our previous real-world analysis of SO initiation in patients on PD in 2014–2015, patients in the completers cohort of the current study were older (55.2 vs. 50.6 years) but were newer to dialysis (19.9 vs. 29.3 months) and had lower sP at baseline (6.26 vs. 6.59 mg/dL).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this real-world retrospective cohort study, PD patients prescribed SO as part of routine clinical care over a 1-year period experienced significant reductions in sP and PB pills per day, and increases in the percentage of patients who achieved sP ≤ 5.5 mg/dL or sP ≤ 4.5 mg/dL, suggesting improved sP management with a concurrent reduction in pill burden. These findings are consistent with our observations in a smaller cohort of patients on PD in 2014–2015 and the results of previous studies in patients on PD or hemodialysis [ 11 13 , 15 , 16 ]. Compared to our previous real-world analysis of SO initiation in patients on PD in 2014–2015, patients in the completers cohort of the current study were older (55.2 vs. 50.6 years) but were newer to dialysis (19.9 vs. 29.3 months) and had lower sP at baseline (6.26 vs. 6.59 mg/dL).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, increases in levels of phosphorus-attuned albumin in the context of no changes in nPCR suggest that SO reduced sP without adverse changes in nutritional status. It has been suggested that dietary intake may improve with SO vs. other binders, given the impact of regimens with higher pill burdens on appetite [ 16 ]. A recent pilot clinical practice study documented similar increases in phosphorus-attuned albumin but did not find any significant changes in patient-reported appetite or dietary intake among PD patients initiating SO [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In data from April 2014 to March 2015, Coyne et al [ 18 ] studied a cohort with a mean baseline sP concentration of 6.93 mg/dL. Using data from May 2018 to May 2019, Rhee et al [ 14 ] and Kendrick et al [ 27 ] studied cohorts with mean baseline sP concentrations of 6.39 mg/dL and 6.38 mg/dL, respectively. These sP concentrations were similar to −1 month concentrations observed in the present analysis (6.25 mg/dL).…”
Section: Discussionmentioning
confidence: 99%